Price selection - Carlos Viana de Carvalho; Oleksiy Kryvtsov (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2021)
Price selection is a simple, model-free measure of selection in price setting and its contribu- tion to in ation dynamics. It exploits comovement between in ation and the level from which adjusting prices departed. Prices that increase from lower-than-usual levels tend to push in a- tion above average. Using detailed micro-level consumer price data for the United Kingdom, the United States, and Canada, we find robust evidence of strong price selection across goods and services. At a disaggregate level, price selection accounts for 37% of in ation variance in the United Kingdom, 36% in the United States, and 28% in Canada. Price selection is stronger for goods with less frequent price changes or with larger average price changes. Aggregate price selection is considerably weaker. A multisector sticky-price model accounts well for this evidence and demonstrates a monotone relationship between price selection and monetary non-neutrality.
Keywords: E31; E51; 330; Consumer Price Index; Inflation; Prices; Selection Effect; Money Non-neutrality